Department of Microbiology, Andhra University, Visakhapatnam, India. - N. BANU,; PAVITHRA. S, (International Journal of Pharma and Bio Sciences, 2015)
Chlorophyllin (CHL), a water soluble sodium salt of Chlorophyll (Chl) is one among the family of phytochemical compounds. CHL is a promising chemopreventive agent believed to block cancer primarily. Commercial grade CHL is available and being used in most research. The idea was to obtain natural Chl derivative CHL and to study its efficiency as an anticancer agent in vitro. The CHL was extracted from the leaves of Morinda citrifolia L. (Noni) and characterized by UV-Visible spectroscopy and Infra-Red Absorption spectroscopy. The anticarcinogenic property of CHL was studied in vitro against two types of cell lines: HepG2 cell lines (Human Hepatocellular carcinoma) and Vero cell lines (African Green Monkey kidney). It was found that the inhibitory effect of CHL was found on cancer cell lines and absent on Vero cell lines. This is the first report on extraction of CHL from fresh leaves of Morinda citrifolia L. and its effect on HepG2 cell lines. The results of the present study show that the CHL extract has a higher safety ratio, which is a good indicator for use in cancer treatment as the extract inhibits only the growth of cancer cells but not normal cells. It also supports for further development of Noni leaves as a neutraceutical or drug.